2020
DOI: 10.1085/jgp.202012679
|View full text |Cite
|
Sign up to set email alerts
|

ECC meets CEU—New focus on the backdoor for calcium ions in skeletal muscle cells

Abstract: In this issue, Michelucci et al. report the existence of specific sites acting as Ca2+ entry units (CEUs) in fast skeletal muscle of mice lacking calsequestrin (CASQ1), the major Ca2+ binding protein of the SR. The CEU provides constitutive and store-operated Ca2+ entry (SOCE) and resistance to force decline resulting from SR Ca2+ depletion during repetitive muscle activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…The sites of STIM1/Orai1 interaction in skeletal muscle fibers has been long debated, as initially it was proposed that SOCE would occur in triads, the intracellular junctions deputed to EC coupling [ 17 ]. Though, this initial hypothesis was not confirmed by recent experimental evidence collected in our laboratory between 2017 and 2020 [ 44 , 47 , 48 , 49 , 50 , 51 , 52 ]. New intracellular junctions named Ca 2+ entry units (CEUs), formed by the association of TT and SR at the I band, were identified as the sites of interaction between STIM1 and Orai1 during SOCE.…”
Section: Introductionmentioning
confidence: 66%
“…The sites of STIM1/Orai1 interaction in skeletal muscle fibers has been long debated, as initially it was proposed that SOCE would occur in triads, the intracellular junctions deputed to EC coupling [ 17 ]. Though, this initial hypothesis was not confirmed by recent experimental evidence collected in our laboratory between 2017 and 2020 [ 44 , 47 , 48 , 49 , 50 , 51 , 52 ]. New intracellular junctions named Ca 2+ entry units (CEUs), formed by the association of TT and SR at the I band, were identified as the sites of interaction between STIM1 and Orai1 during SOCE.…”
Section: Introductionmentioning
confidence: 66%
“…A commentary published in J. Gen. Physiol. proposed CEUs as the backdoor for Ca 2+ ions in muscle cells, bringing new attention to the importance of external Ca 2+ in the function skeletal fibers [208].…”
Section: Calcium Entry Units (Ceus): the Dynamic Junctions That Media...mentioning
confidence: 99%
“…While there was always general agreement about the important role that SOCE plays in limiting muscle fatigue [ 40 , 41 , 50 , 51 , 77 ], exactly how and where STIM1/Orai1 interact to allow Ca 2+ entry in skeletal muscle fibers has been debated for several years. Recent experimental evidence collected in our laboratory indicated that intracellular junctions, named Ca 2+ Entry Units (CEUs), formed by the association of SR and TT at the I band, are the most likely sites of interaction between STIM1 and Orai1 during SOCE [ 77 , 78 , 79 , 80 , 81 , 82 , 83 ]. CEUs are few and small in control conditions (the main reason that did not allow their prompt identification), but increase in number and size during exercise [ 77 ] to then disassemble following recovery [ 81 ].…”
Section: Introductionmentioning
confidence: 99%